Overview of self-medication pharmaceutical preparations by the public - Sulfiyana H. Ambo Lau (Jurnal Ilmiah Kesehatan Sandi Husada, 2024)
Introduction: self-medication is an effort made by an individual to obtain medication and use it without diagnosis, prescription, supervision or consultation with a doctor in an effort to treat certain minor illnesses. Self-medication is self-medication without a doctor's prescription. In disease treatment, risks such as misdiagnosis, use of excessive drug doses, and long-term use can cause adverse effects on patients. Objective: to determine the description of the use of self-medicated pharmaceutical preparations by the public. Methods: This type of research uses a descriptive method, namely research that includes surveys with data collection in the form of questionnaires with a total of 81 respondents. The sampling method uses Non-Probability Sampling with Purposive Sampling techniques using a questionnaire using an open-ended questionnaire format in collecting data and recording reports. Result: results of research data collection, that the description of the use of pharmaceutical preparations by self-medication in the Bung Permai Housing Community is that 81 respondents (100.00%) carry out self-medication, the source of drug information is from print and electronic media, namely 36 respondents (44.45%) , the place of purchase of medicine was at the pharmacy/clinic, namely 43 respondents (53.02%), the disease suffered was fever, 23 respondents (28.40%), and the pharmaceutical preparation used was paracetamol, 27 respondents (33.33%). Conclusion: that the description of the use of pharmaceutical preparations by self-help in the Permai Community Housing is mostly self-medication. Therefore, there is a need for better education and supervision of the use of pharmaceutical preparations independently in order to increase understanding and safety in self-medication. It is hoped that in the future there will be research on public knowledge and behavior regarding self-medication of pharmaceutical preparations so that changes in respondents' knowledge and behavior can be seen after being given good and correct information.